Histone Deacetylase 2 Knockdown Ameliorates Morphological Abnormalities of Dendritic Branches and Spines to Improve Synaptic Plasticity in an APP/PS1 Transgenic Mouse Model - Nakatsuka, Daiki; Izumi, Takaya; Tsukamoto, Tasuku; Oyama, Miki; Nishitomi, Kohei; Deguchi, Yuichi; Niidome, Kazuki; Yamakawa, Hidekuni; Ito, Hisanori; Ogawa, Koichi (Frontiers in Molecular Neuroscience, 2021)
Disease-modifying therapies, such as neuroprotective and neurorestorative interventions, are strongly desired for Alzheimer’s disease (AD) treatment. Several studies have suggested that histone deacetylase 2 (HDAC2) inhibition can exhibit disease-modifying effects in AD patients. However, whether HDAC2 inhibition shows neuroprotective and neurorestorative effects under neuropathic conditions, such as amyloid β (Aβ)-elevated states, remains poorly understood. Here, we performed HDAC2-specific knockdown in CA1 pyramidal cells and showed that HDAC2 knockdown increased the length of dendrites and the number of mushroom-like spines of CA1 basal dendrites in APP/PS1 transgenic mouse model. Furthermore, HDAC2 knockdown also ameliorated the deficits in hippocampal CA1 long-term potentiation and memory impairment in contextual fear conditioning tests. Taken together, our results support the notion that specific inhibition of HDAC2 has the potential to slow the disease progression of AD through ameliorating Aβ-induced neuronal impairments.